THE IMPACT OF GREEN FINANCE, TRADE OPENNESS, AND FOSSIL FUEL SUBSIDIES ON RENEWABLE ENERGY CONSUMPTION: A GLOBAL AND ASIA-PACIFIC PERSPECTIVE - Fitjriyah, Alya Ryanti; Dwiputri, Inayati Nuraini (UI Scholars Hub, 2025)
Fossil fuels are the major source of global emissions, with the Asia-Pacific region being the climate biggest polluter. Despite the global efforts to shift to cleaner energy, fossil fuels still dominate the energy mix. Therefore, renewable energy adoption needs to be encouraged more to improve economic sustainability. The Glasgow Climate Pact emphasises the importance of helping developing countries in addressing the climate change issue through financial support, capacity building, and technology transfer. Hence, this study examines the influence of green finance, open trade, and fossil fuel subsidies on renewable energy adoption in 38 countries from 2017 to 2023. By using dummy variables, this study makes a unique contribution by highlighting regional disparities, particularly in the Asia-Pacific region. To address heteroskedasticity, autocorrelation, and cross-sectional dependence in the model, this study used PCSE (Panel-Corrected Standard Errors) and FGLS (Feasible Generalised Least Squares). Four main findings emerged from this study: (1) Green finance significantly drives the adoption of renewable energy, indicating its potential as an important element in the transition effort towards cleaner energy sources. (2) Trade openness, Gross Domestic Product (GDP), and government effectiveness have different effects on renewable energy utilisation, indicating their impact depends on the regional context. (3) Fossil fuel subsidies hinder the adoption of renewable energy, underscoring the importance of reforming these subsidies to accelerate the transition to renewable energy. (4) The Asia-Pacific region lags behind other regions in renewable energy utilisation, showing the unique structural and policy challenges to the region. These findings suggest the need for more green finance instruments, cross-border cooperation, and reduced fossil fuel subsidies, especially in developing countries and the Asia-Pacific region, to achieve global climate goals. This research emphasises the importance of technology transfer and capacity building to facilitate the transition to renewable energy. However, the short panel period in this study may obscure long-term trends. Thus, future research could extend the period and add more variables such as the role of energy storage, ESG framework, and environmental innovation in facilitating the transition to renewable energy.